Causative variant profile of collagen VI-related dystrophy in Japan - Inoue, Michio (Orphanet J Rare Dis, 2021)
BACKGROUND: Collagen VI-related dystrophy spans a clinical continuum from severe Ullrich congenital muscular dystrophy to milder Bethlem myopathy. This disease is caused by causative variants in COL6A1, COL6A2, or COL6A3. Most reported causative variants are de novo; therefore, to identify possible associated causative variants, comprehensive large cohort studies are required for different ethnicities. METHODS: We retrospectively reviewed clinical information, muscle histology, and genetic analyses from 147 Japanese patients representing 130 families, whose samples were sent for diagnosis to the National Center of Neurology and Psychiatry between July 1979 and January 2020. Genetic analyses were conducted by gene-based resequencing, targeted panel resequencing, and whole exome sequencing, in combination with cDNA analysis. RESULTS: Of a total of 130 families with 1–5 members with collagen VI-related dystrophy, 120 had mono-allelic and 10 had bi-allelic variants in COL6A1, COL6A2, or COL6A3. Among them, 60 variants were in COL6A1, 57 in COL6A2, and 23 in COL6A3, including 37 novel variants. Mono-allelic variants were classified into four groups: missense (69, 58%), splicing (40, 33%), small in-frame deletion (7, 6%), and large genomic deletion (4, 3%). Variants in the triple helical domains accounted for 88% (105/120) of all mono-allelic variants. CONCLUSIONS: We report the causative variant profile of a large set of Japanese cases of collagen VI-related dystrophy. This dataset can be used as a reference to support genetic diagnosis and variant-specific treatment.